PENGARUH DANA DESA, ALOKASI DANA DESA DAN DANA ALOKASI UMUM TERHADAP KEMISKINAN DI PROVINSI JAWA TIMUR TAHUN 2015-2016 - diana wijaya; Zainal Arifin; Syamsul Hadi (Jurnal Ilmu Ekonomi JIE, 2018)
The purpose of this research is to know the development and influence of DD, ADD, and DAU Kab / Kota to poverty in East Java 2015-2016. The analysis tool used is panel data regression which then performed hypothesis testing with F test, t test, and Coefficient of Determination (R2) at error rate ɑ = 5%. The result of analysis of penel data with selected model is Fixed Effect Model shows that there is poverty development in East Java between 2015 and 2016, the variables used in the model are DD, ADD, and DAU have an effect on poverty with value of 0.04 for DD, -0.04 ADD,  and for DAU 0.18. While the value of coefficient of determination (R2) is 0.99 or 99%, it shows that the ability of variable DD, ADD, UMK and DAU in describing poverty in East Java province equal to 99%.Keywords: Village Funds, Allocation Of Village Funds, General Allocation Funds, Poverty Kab/Kota provinsi Jawa Timur